Perilaku Ibu Rumah Tangga dalam Pengelolaan Sampah Rumah Tangga di Kecamatan Kemiling - Imam Ashari; Irwan Effendi; Wuryaningsih Dwi Sayekti; Yaktiworo Indriani; Muhammad Ibnu (Fakultas Pertanian, Universitas Lampung, 2025)
Waste is a major problem today. The more the population, the more waste is produced. Waste accumulation in Indonesia reaches 21.6 million tons per year in 2022. It is recorded that in Lampung Province in one year there are 1.6 million tons of waste per year in 2022. Activities carried out by housewives are closely related to activities in the kitchen, from these activities waste is produced which will later be managed by housewives, therefore the behavior of housewives in waste management is very important. This study aims to determine the behavior of housewives in waste management, find out the income of housewives from waste management and analyze the relationship between X and Y. The research method used is a survey method. This study was conducted in Kemiling District, Bandar Lampung City, Lampung Province. Data collection was February-April 2025. The population in this study was 261 members of the housewife group, obtained 72 housewives. The data used were primary data and secondary data. The data analysis method used was descriptive quantitative with rank-spearman analysis. The results of this study indicate that housewives' behavior in waste management is categorized as good based on knowledge, attitudes, and skills. Housewives' income from waste management is low. Housewives' behavior in waste management is related to their income.